Kosmologi dalam Pemikiran Ikhwan al-Shafa - Fajarini, Shinta Dewi (Mazalat: Jurnal Pemikiran Islam, 2026)
This article analyzes the cosmological thought of Ikhwan al-Shafa, a group of philosophers who made significant contributions to the tradition of Islamic thought. In their work, al-Rasa'il, they present the theory of emanation, which indicates that everything originates from God as the primary source. Ikhwan al-Shafa emphasizes the unity and interconnectedness between the universal soul and the physical body, as well as introducing the concept of universal natural law that governs interactions within the universe. Furthermore, they view humans as a microcosm that reflects the macrocosm, affirming the harmonious relationship between humanity and the universe. This research aims to reveal the relevance of their thought in the context of cosmology and spirituality, as well as its impact on contemporary thought.